Program to improve qur’anic reading skills for teachers at raudhatul athfal and integrated islamic kindergarten, Deli Serdang - Rahmita, Nelly; Sit, Masganti; Rakhmawati, Fibri (Universitas Islam Negeri Raden Intan Lampung, 2025)
Background : The ability to read the Qur’an correctly is a fundamental skill that must be developed by teachers of Early Childhood Islamic Education (PIAUD). Variations in educational background and teaching experience regarding Qur’anic learning result in differing levels of Qur’anic reading proficiency among teachers. Therefore, a Qur’an reading enhancement program based on tahsin and tahfizh is necessary to address this gap. Aim : This study aims to examine the implementation of a Qur’anic reading improvement program for teachers based on tahsin and tahfizh methods. Method : This study employs a descriptive qualitative method using a multi-site approach, focusing on two institutions: Raudhatul Athfal Al-Ikhlas Kongo and TK Islam Terpadu Jabal Noor. Result : This study reveals that the program planning includes a Qur’anic reading proficiency test for class placement, a structured plan for regular Qur’an reading training, and a set evaluation schedule. The implementation is carried out systematically, with the talaqqi method focused on Juz 30. Evaluation involves monitoring progress in Qur’anic recitation, with emphasis on tajwīd, makhārij al-ḥurūf, and waqf–ibtidā’. The results of implementation show positive impacts in three main areas: Teachers’ understanding of tahsin, Practical skills in Qur’anic reading, Improved memorization and a more positive attitude toward tahsin and tahfīzh instruction. Supporting factors include internal elements such as motivation, attitude, and personal readiness of teachers. External factors encompass mentorship, institutional policies, and learning facilities. Inhibiting factors involve limited time, varied initial reading abilities, and inconsistency in independent practice. Conclusion : This research is a Qur’an reading improvement program for teachers at Raudhatul Athfal Al-Ikhlas Kongo and TK Islam Terpadu Jabal Noor. The program has shown promising results; however, regular evaluations are necessary to monitor progress and adjust the applied methods as needed.